2018
DOI: 10.1038/s41431-018-0187-2
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic spectrum of Au–Kline syndrome: a report of six new cases and review of the literature

Abstract: Au-Kline syndrome (AKS, OMIM 616580) is a multiple malformation syndrome, first reported in 2015, associated with intellectual disability. AKS has been associated with de novo loss-of-function variants in HNRNPK (heterogeneous ribonucleoprotein K), and to date, only four of these patients have been described in the literature. Recently, an additional patient with a missense variant in HNRNPK was also reported. These patients have striking facial dysmorphic features, including long palpebral fissures, ptosis, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 12 publications
(43 reference statements)
1
36
0
Order By: Relevance
“…Patients with OS and AKS experience a variety of symptoms including neurological abnormalities and internal anomalies. As Au et al () reported that the genitourinary system associated with morbidity and mortality in patients with AKS, our two original patients with severe congenital hydronephrosis died at an early age.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Patients with OS and AKS experience a variety of symptoms including neurological abnormalities and internal anomalies. As Au et al () reported that the genitourinary system associated with morbidity and mortality in patients with AKS, our two original patients with severe congenital hydronephrosis died at an early age.…”
Section: Discussionmentioning
confidence: 61%
“…Au et al () reported a new syndrome (AKS) due to loss‐of‐function variants in HNRNPK . They (Au et al, ) summarized 12 patients with AKS. The patients with AKS have dysmorphic features, including long palpebral fissures, ptosis, a deeply grooved tongue, broad nose, and down‐turned mouth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenotypic spectrum of individuals with HNRNPK mutations was further delineated over the next few years and these patients were subsequently called "AKS." AKS was defined by the association of hypotonia, developmental delay, moderate-to-severe intellectual disability, facial dysmorphic features, autonomic dysfunction, congenital heart disease, hydronephrosis, palate abnormalities, oligodontia, and inconstant craniosynostosis or other skeletal anomalies (Au et al, 2018). The close similarities between OS and AKS were then noted by Dr Okamato in his recent paper (Okamoto, 2019).…”
mentioning
confidence: 99%